FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KELAPA DALAM (COCOS NUCIVERA L) DI KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR - Ardi, Hariyanto; Iyan, Ritayani; Aqualdo, Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study in kecamatan reteh kabupaten indragiri hilir e research problem is: 1) What factors are affecting the income of coconut farmers in the district Reteh Indaragiri Hilir Regency? 2) What is the most significant factor affecting the income of coconut farmers in the district in Indragiri Hilir Reteh? this study attempts to know : what are affecting income coconut farmers in the cocos nucivera l ) in kecamatan reteh kabupaten indragiri hilir.To know factors what most significant to affect income coconut farmers in kecamatan reteh kabupaten indragiri hilir.A method of the sample used is the method technique snowballs ( snowball sampling ), where a population of a total of 44 coconut farmers who study. The methods used in this research is a descriptive percentage analysis methods and quantitative analysis i.e. analysis simultaneously (F test), and partial (t-test) with the help of the program SPSS 16). The data used in this study is the amount of labor, the number of price, the amount of land area, and the production of Reteh in the County of Indragiri Hilir. The result of the analysis show that (1) simultaneously variable labor, price, land area and number of influential production significantly to coconut farmers income variables. Partially labor, price, land area and the amount of production effect on farmer income variable in Reteh Regency coconut Indragiri Hilir. (2) the variable labor and land area significant effect against coconut farmer income in Indragiri Hilir Regency Reteh District.Keywords : Labor, Price, Production, and Land Area.